APPLYING DECONSTRUCTION ANALYSIS TO DEVELOP VOCABULARY OF THE SECOND SEMESTER STUDENTS OF ENGLISH DEPARTMENT AT COKROAMINOTO UNIVERSITY OF PALOPO - F. Felogau (Universitas Sembilanbelas November Kolaka, 2017)
This research aims: (1) To find out whether or not the use of deconstruction analysis effective to develop the students’ vocabulary in word formation, word meaning and word usage and (2) to find out the aspect which is mostly affected by using deconstruction analysis. This research employed quasi experimental design. The population of this research was the second semester students of English department at Cokroaminoto University Palopo, which consisting of seven classes in 2013/2014 academic year. The total number of population was 300 students. This research used purposive sampling. The samples of this research, one class was as an experimental class and the other was as a control class. The samples of each class were 30 students. The research data was collected by using vocabulary test to get the students’ vocabulary achievement in covering word formation, word meaning and word usage, which were analyzed by inferential statistic through SPSS version 17 for windows program. The students’ result of posttest of experimental group is significantly developed than the students’ result of posttest of control group by the mean score 76.22 37.55. The difference of both scores is statistically significant based on the t-test value at significant level 0.05 in which the probability value is lower than the significant level (0.00 0.05). So, H1 was accepted and H0 was rejected. Then, the three aspects (word formation, word meaning, and word usage) have the same average score, the score of F-obs (1.64) was smaller than F-table (2; 87; 0.05) was 3.10 or 1.64 3.10. So, in this case H1 was rejected and H0 was accepted. It can be concluded that the use of deconstruction analysis effective to develop the students’ vocabulary in word formation, word meaning and word usage and the three aspects have the same average score. So, there is no that mostly affected by using deconstruction analysis